Study of barrier effect in dielectrics; 1-st International Congress on Radiation Physics, High Current Electronics, and Modification of Materials; Vol. 1: 11-th International Conference on Radiation Physics and Chemistry of Condensed Matter - Lebedev S. M. Sergey Mikhailovich (2000, 2000)
The results of the barrier effect study in gaseous and solid dielectrics in divergent and quasi-uniform electric fields are presented in this paper. The influence of various factors such as the position of the barrier in gap, the change of permittivity and conductivity either on the breakdown voltage and breakdown time in the quasi-uniform field or on the tree-initiation time in the divergent field was investigated. Application of barriers with high permittivity may result in a significant increase in breakdown voltage and breakdown time. An analysis of existing models of the barrier effect is presented